Prognostic nomogram for cancer-specific survival in patients with intrahepatic cholangiocarcinoma after hepatectomy: A population study of 919 patients - Huang, Gaobo; Song, Weilun; Zhang, Yanchao; Ren, Bingyi; Lv, Yi; Liu, Kang (Frontiers in Surgery, 2023)
Background and Aims: Intrahepatic cholangiocarcinoma has an increasing global incidence and mortality rate. Hepatectomy is still the most effective curative treatment for patients with ICC, but the prognosis of patients with ICC is still poor even after curative resection. This study aimed to incorporate important factors obtained from SEER database to construct and validate a nomogram for predicting the cancer-specific survival of patients with ICC after hepatectomy. Methods: We obtained patient data from SEER database. The nomogram was constructed base on six prognostic factors for predicting CSS rates in ICC patients. The nomogram was validated by C-index, ROC curve and calibration curves. Results: A total of 919 patients with ICC after hepatectomy between 2000 and 2018 were included in this study. A nomogram based on six independent prognostic factors (Black race, AJCC T, AJCC N, AJCC M, chemotherapy and PLNR  0.15) was developed for the prediction of CSS at 3 and 5 years. The C-index of the nomogram and AJCC stage system were 0.709 and 0.657 in the training cohort respectively. The 3- and 5-year AUCs of nomogram were 0.744 and 0.75 in the training cohort. The calibration plots indicated that there was good agreement between the actual observations and predictions. Conclusions: In conclusion, we constructed and validated a nomogram for predicting the 3- and 5-year CSS in ICC patients after hepatectomy. We have confirmed the precise calibration and acceptable discrimination power of our nomogram. The predictive power of this nomogram may be improved by considering other potential important factors and also by external validation.